Creating and Sustaining Superior Performance of Hospitals in Coimbatore - Raman, D.N.; Balaji Prasad, M. (Indian Journal of Marketing, 2005)
Health Care is fundamental to the quality of life. Health is that condition of the individual that makes possible the relishment of the highest enjoyment of life.The World Health Organization defines health as "A state of complete physical, mental and social well being and merely absence of disease of infirmity".Development of Human Resource is as important to economic growth as industries and services. Â Hospitals, the key element in any health care system, being the centers of specialized medicine and technology with multi disciplinary teams, delivers a whole range of specialized services. Moreover, hospitals play an important role in health promotions, environmental concern, social human resources, creation of patient orient services and management.